Late and Severe Myopathy in a Patient With Glycogenosis VII Worsened by Cyclosporine and Amiodarone - Filosto, Massimiliano; Cotti Piccinelli, Stefano; Pichiecchio, Anna; Musumeci, Olimpia; Galvagni, Anna; Caria, Filomena; Gallo Cassarino, Serena; Baldelli, Enrico; Vitale, Raimondo; Padovani, Alessandro; Toscano, Antonio (Frontiers in Neurology, 2019)
Glycogenosis VII (GSD VII) is a rare autosomal recessive glycogen storage disorder caused by mutations in the PFKM gene encoding the phosphofructokinase (PFK) enzyme. A classical form with exercise intolerance, contractures and myoglobinuria, a severe multisystem infantile form, an hemolytic variant and a late-onset form usually presenting with muscle pain and mild fixed proximal weakness have been reported. We describe a 65-year-old man affected by muscle PFK deficiency who, since the age of 33, presented with exercise intolerance and myoglobinuria. Muscle biopsy showed a vacuolar myopathy with glycogen storage. The biochemical assay of PFK-M showed very low residual activity (6%). Genetic analysis of PFKM gene evidenced the presence of the heterozygote c.1817A>C (p.Asp543Ala) and c.488 G>A (p.Arg100Gln) pathogenic mutations. In his fifth decade, he started cyclosporine after liver transplantation for hepatocellular carcinoma and, then, amiodarone because of atrial fibrillation. In the following years, he developed a progressive and severe muscle weakness, mainly involving lower limbs, up to a loss of independent walking. Muscle MRI showed adipose substitution of both anterior and posterior thigh muscles with selective sparing of the medial compartment. Marked signs of adipose substitution were also documented in the legs with a selective replacement of gemelli and peroneus muscles. The temporal relationship between the patient’s clinical worsening and chronic treatment with cyclosporine and amiodarone suggests an additive toxic damage by these two potentially myotoxic drugs determining such an unusually severe phenotype, also confirmed by muscle MRI findings.